LEGAL CHARACTERISTICS OF INTERNATIONAL FINANCIAL ORGANIZATIONS AS SUBJECTS OF FINANCIAL ACTIVITY IN UKRAINE - Kuzmin, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: determination of the legal nature of the financial activity of international financial organizations in Ukraine. Research methods: general scientific and special legal methods. The application of the descriptive method made it possible to characterize the concept and legal nature of state financial activity. The main principles of financial activity were analyzed using the formal legal method. Using the logical method, the concepts of "financial system" and "international finance" were formulated. Results: it was concluded that the concept of "financial activity" is understood as the division of funds into public and private funds and their interaction within the limits of financial law. The term "financial activity of the state" can be defined as the public activity of the relevant state bodies regarding the creation, distribution and use of centralized monetary funds and the creation of optimal and motivating conditions for the creation, distribution and use of decentralized monetary funds in the context of the state’s performance of the tasks assigned to it. Also, as a result of the discussions, various scientific positions are expressed regarding the consequences (primarily negative for the country and society as a whole) of cooperation between Ukraine and international financial organizations. The influence of the process of globalization on the financial system of Ukraine is analyzed. The essence of the concept of "financial system" and its main components have been studied. The status of international financial institutions in the financial system of Ukraine, their influence on national financial and economic indicators, trends of cooperation with such organizations and institutions as the International Monetary Fund, the International Bank for Reconstruction and Development, the European Investment Bank and others are determined. Discussion: search for ways to overcome existing problems in the implementation of financial activities of international financial organizations in Ukraine.